Management of the Development Character Program for Students in Supporting the Independence of Islamic Boarding Schools - Asep Supriatna; Imam Abdullah; Fadli Rais; Mowafg Abrahem Masuwd; Diah Widiawati; Agus, Agus; Neneng Nurhasanah (CV. Creative Tugu Pena, 2025)
The development of students' character is an important aspect in Islamic boarding school education which aims to form independent, disciplined, and noble individuals. Manbaul Ulum Islamic Boarding School applies various strategies in building students' character through habituation programs, role models, and extracurricular activities. This study aims to analyze the management of the student character development program at Manbaul Ulum Islamic Boarding School, including strategies, challenges, and their impact on students' independence. This study uses a qualitative method with a case study approach. Data were collected through in-depth interviews with the boarding school caretaker, ustadz, and students, direct observation, and documentation. Data analysis was carried out using data reduction techniques, data presentation, and drawing conclusions. The results of the study indicate that the management of the character development program at Manbaul Ulum Islamic Boarding School is carried out systematically through careful planning. The role model method and mentoring system are the main strategies in forming students' character. However, there are obstacles such as limited resources, differences in students' backgrounds, and a less than optimal evaluation system. The implications of this study indicate that the success of the character development program for students depends on the synergy between Islamic boarding school managers, educators, and the social environment of this Islamic boarding school. The contribution of this research is to provide an empirical description and theoretical basis for designing an integrative and adaptive Islamic boarding school character development program to the challenges of the times.